Ensaios sobre resiliência econômica regional no Brasil - Eberhardt, Paulo Henrique de Cezaro (2021)
The purpose of the essays that make up this thesis was to analyze the differentiated regional impact of economic crises. In recent literature, it has been argued that this differentiated regional impact to call regional resilience, using the term resilience initially used in biology and engineering. The first essay uses the notion of resilience of ecology to identify how the Brazilian mesoregions reacted to the 2008 and 2014/2016 crises. For this, the seemingly unrelated regression model (SUR) was used, which makes it possible to identify the impact of crises in each region. In the second essay, the notion of engineering resilience was used to address the duration of the crisis in each Brazilian micro-region in the 2008 crisis using survival analysis, with the Kaplan-Meyer model and estimating Cox regression, which allows add covariables to explain the characteristics that make a region resilient. In the third essay, the resilience of the regions was analyzed through a negative trade shock. To this end, spatial econometric models were used to observe the effects that imports have on formal employment in brazilian regions.